ESTRUTURAÇÃO DE PROJECT FINANCE COM FINANCIADORES INTERNOS E EXTERNOS: ESTUDO DE CASO DE UM PROJETO TERMELÉTRICO - Silva, José Luiz Pereira Duarte (2010)
This work has for goal to investigate an enterprise financed in the Project Finance modality through a study of a real case and show the complexity of this financing technique, talking about the inherent risks by the adoption of multiple resources of funds and its conflicts. The target project was the thermoelectric unit Termopernambuco, whose construction started in 2000 and finished in 2004, receiving financial recourses from Interamerican Development Bank (IDB) and Banco Nacional de Desenvolvimento Econômico e Social (BNDES). This study is the result of a widespread research accomplished in books, thesis, others dissertations, texts published by specialists and available materials that deal with the theme. A case study portrays the complexity of financing structuring in Project Finance modality and the several structuring costs of its utilization. At the end, it s possible to see the current financial impacts of the dissonance among the third party resources entrance, represented by the alteration of capitation cost.